Challenges of integrating evidence into health policy and planning: linking multiple disciplinary approaches - Carmen Huckel Schneider; Fiona Blyth (Public Health Research & Practice, 2017)
Objectives: To explore the challenges that arise through the multidisciplinary nature of evidence informed policy making (EIPM).